Understanding the Role of the BAI Subfamily of Adhesion G Protein-Coupled Receptors (GPCRs) in Pathological and Physiological Conditions - Moon, Sun Young (Genes (Basel), 2018)
Brain-specific angiogenesis inhibitors (BAIs) 1, 2, and 3 are members of the adhesion G protein-coupled receptors, subfamily B, which share a conserved seven-transmembrane structure and an N-terminal extracellular domain. In cell- and animal-based studies, these receptors have been shown to play diverse roles under physiological and pathological conditions. BAI1 is an engulfment receptor and performs major functions in apoptotic-cell clearance and interacts (as a pattern recognition receptor) with pathogen components. BAI1 and -3 also participate in myoblast fusion. Furthermore, BAI1–3 have been linked to tumor progression and neurological diseases. In this review, we summarize the current understanding of the functions of BAI1–3 in pathological and physiological conditions and discuss future directions in terms of the importance of BAIs as pharmacological targets in diseases.